Pengembangan Perangkat Pembelajaran Berbasis Diferensiasi dalam Pembelajaran Biologi Pada Kelas X SMA Negeri 16 Bone - Suhaeri Suhaeri; Firdaus Daud (Universitas Negeri Makassar, 2022)
This study is a development research (Research & Development) which aims to examine the level of validity, practicality, and effectiveness of the Differentiation-Based Learning devices. The development process of differentiation-based learning refers to the 4-D model development model by Thiagarajan. This study was conducted at SMAN 16 Bone with 30 students of grade X MIA 1 and 2 Biology teachers as the research subjects. The research instrument employed learning device validation sheet, teachers’ response questionnaires, students’ response questionnaires, implementation observation sheets, and the test instruments in the form of multiple choice questions. Data of validity and practicality levels were collected by using questionnaires and data of the effectiveness level using the learning outcomes test. Data collection techniques consisted of non-test and test techniques. The results of the study reveal that the learning devices which include the lesson plans, LKPD, media, and THB are valid, practical, and effective in improving students' learning outcomes skills. The learning devices are in fully implemented category, the responses of teachers and students are in very practical and practical category. The learning devices are categorized as effective with the completeness of the learning outcomes test of 82.4% each.